Highly Stable Perylenediimide‐Based Self‐Assembled Monolayers Studied with Spectroelectrochemistry. Issue 6 (11th March 2016) - Bkhach, Sihame; Le Duc, Yann; Alévêque, Olivier; Gautier, Christelle; Hudhomme, Piétrick; Levillain, Eric
Abstract: Perylenediimide (PDI)‐based self‐assembled monolayers (SAMs) have been studied by using quartz crystal microbalance, X‐ray photoelectron spectroscopy, cyclic voltammetry, and spectroelectrochemistry (SEC). The high stability of PDI‐based SAMs has allowed very low signals to be probed by using absorption and emission SEC and by extracting voltabsorptograms. The wavelengths are reported for the absorption maxima of the PDI, anion radical, and dianion species. In contrast, the magnitudes of the molar extinction coefficient of the reduced forms were not preserved in the SAM. The quenching of PDI fluorescence was confirmed on a gold substrate. Abstract : Tailor made : The first absorption and fluorescence spectroelectrochemical studies on perylenediimide‐based self‐assembled monolayers are reported. These experiments are carried out by using quartz crystal microbalance, X‐ray photoelectron spectroscopy, cyclic voltammetry, and spectroelectrochemistry.